Impact of Microsetella norvegica on carbon flux attenuation and as a secondary producer during the polar night in the subarctic Porsangerfjord - Mooney, Benjamin Paul; Iversen, Morten Hvitfeldt; Norrbin, Maria Fredrika (Frontiers in Marine Science, 2023)
It is known that Microsetella norvegica feed on phytoplankton and provide an important link to higher trophic levels in Arctic fjords, such as fish sprat (Sprattus sprattus) and three-spined stickleback (Gasterosteus aculeatus). It has recently been suggested that M. norvegica may also contribute substantially to carbon flux attenuation during periods of high abundance. However, we still know very little about how seasonal variations in abundance and vertical distribution of M. norvegica impact the efficiency of the biological carbon pump in Arctic fjords. We investigated the role of Microsetella norvegica, a small harpacticoid copepod, for particulate organic carbon flux attenuation via aggregate feeding in a subarctic fjord. We quantified the vertical distribution and abundance of M. norvegica, phytoplankton, and marine snow simultaneously with a Digital Autonomous Video Plankton Recorder in Porsangerfjord, northern Norway, between August 2013 and November 2014. We estimated the highest abundance of M. norvegica as 4.86x106 individuals m-2 in October. Our results suggest that M. norvegica preferred diatoms over both marine snow and the prymnesiophyte Phaeocystis pouchetii during euphotic bloom conditions. However, during oligotrophic conditions when phytoplankton were scarce, M. norvegica switched to marine snow as a food source. M. norvegica has the potential to explain 1.4% and 0.29% of the total carbon flux attenuation in October and November, respectively. These results suggest that small copepods feed on settling detritus when no alternative food is available. Detritus feeding by M. norvegica may have an ecological impact during the polar night, both via direct carbon flux attenuation, but also as secondary producers in periods with low primary production. Currently small copepods such as M. norvegica are not included in carbon budgets or large-scale modelling, but considering their potentially high abundance they may represent an important but overlooked pathway in both the carbon cycle and trophic level interactions.